Transmission Line Protection and Fault Location Based on Travelling Wave Measurement - Siozinys, V.; Urniezius, R. (Elektronika ir Elektrotechnika, 2013)
Last decade power systems have faced blackouts. Also smart grid concepts are developing to increase overall system performance. The need and the challenge is high accuracy distance to the fault measurement algorithm in transmission line protection. The article describes differential travelling wave protection also as distance to the fault measurement principles. The distance to the fault calculation deviations are investigated, also as classified as the stochastic and systematic. The systematic deviation elimination methods are described. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5645